Reduced calcification and osteogenic features in advanced atherosclerotic plaques of mice with macrophage-specific loss of TRPC3 - Dube, Prabhatchandra R. (2018)
Fil: Dube, Prabhatchandra R. University of Toledo. College of Medicine and Life Sciences. Center for Hypertension and Personalized Medicine. Department of Physiology and Pharmacology; Estados Unidos